Genetic variation of the human ACE and ACTN3 genes in connection with VO2max among Hungarian elite athletes - Bosnyák, E.; Trájer, E.; Udvardy, A.; Protzner, A.; Komka, Z.; Györe, I.; Tóth, M.; Szmodis, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Nowadays it is well recognized that athletic performance highly depends on genetic background. Among those, angiotensin-converting enzyme (ACE) and the á-actinin-3 (ACTN3) genes are considered strong candidate genes associated with human physical performance, although their influence has not been described completely. The aim of our study was to evaluate the differences of these genetic variants and to reveal possible connections between the gene polymorphisms` combinations and the Vo2max values. Methods: The study involved 155 Hungarian elite athletes from endurance, team, middle-distance and power sports. Human genomic DNA was isolated from blood, genotyping was performed by polymerase chain reaction. The examination consisted of a vita maxima test to exhaustion on treadmill with constant velocity (10 km/h) starting from a 1,5 % gradient ascending with 1,5 % every minute. During the examination we registered the maximal oxygen uptake (Vo2max). To measure the differences between the groups One-way Anova and Tukey HSD tests were performed using Statistica 9.0 for Windows® (significance level: p<0,05). Results: Only 2% of the athletes (all of tem are kayaking/canoeing athletes) had the combination of ACE II and ACTN3 XX genotypes with the average Vo2max value of 56.23 ml/kg/min, which was the lowest value. ACTN3 XX genotype was the least frequent in the whole sample compared to the other ACTN3 genotypes. We found significant differences between each group apart from the case of kayaking/canoeing vs. power athletes considering the average Vo2max values. Athletes with both ACTN3 XX and ACE DD genotypes had the highest Vo2max values (64.53 ml/kg/min) but there were no significant differences while comparing them with the other 8 combination. In the team sports the ACTN3 R alelle occurrence was clearly dominant, whereas only 15% of these athletes presented XX genotype. 4 out of the highest 5 Vo2max results (avg: 80.56 ml/kg/min) i were presented by athletes possessing ACE ID+ACTN3 RR genotype combination. Discussion: The connection of the ACE I allele to the endurance performance has been published many times. It is well known that high maximal oxygen uptake volumen is essential for a long-distance athlete. Despite this statement we found the lowest Vo2max values in the ACE II + ACTN3 RR/RX/XX group, but there were no significant differences comparing these values to that of other groups` results. Furthermore, only 8% of the athletes in the endurance group have ACE II genotype, which - based on the literature - would be preferable. The R allele is "responsible" for sprint and power. In team sports speed and muscular strenght play a very important role: the ACTN3 RR genotype and R allele occurrence were determinant in this group.